EFFECTS OF COMORBIDITY IN PERSONS WITH MULTIPLE SCLEROSIS - Marić, Gorica; Pekmezović, Tatjana; Lalić, Katarina; Mesaroš, Šarlota; Drulović, Jelena (Medicinski podmladak, 2019)
Comorbidity is one of major patients’ characteristics, together with genetics, age, gender, race, ethnicity, and socioeconomic status, relevant to the clinical presentation and management of MS. The main goal of investigation of comorbidities in persons with MS is to improve the outcome of the disease and general health of the patients. It is estimated that one in three MS patients is suffering from some physical comorbidity, while more than half of them experience psychiatric comorbidity during course of the disease. Recent systematic reviews revealed that among physical comorbidities, the most prevalent are hypertension, hypercholesterolemia and chronic lung disease, while among psychiatric comorbidities depression and anxiety are the most frequent. Moreover, it was found that the presence of physical comorbidities is associated with the greater risk for occurrence of mental comorbidities. Although physical and mental comorbidities are increasingly recognized as relevant to clinical outcomes, gaps in the understanding of epidemiological aspects of comorbidity in MS still remain. It is clear that several potential benefits can be gained from the study of comorbidities in patients with MS, including improved prognosis, individualized disease management, insights into the etiology and pathogenesis of MS, and new treatment approaches. Natural history studies conducted so far have focused on the prognostic value of clinical characteristics of this disorder, however inclusion of comorbidity information could improve prognosis by explaining heterogeneity in disease outcomes, which would enable clinicians to provide individual patients with better information about the clinical course of their disease and to make informed treatment choices. Early identification and treatment of modifiable comorbid conditions represents a promising point of MS care which could potentially delay development of sustained worsening disability and improve overall quality of life.